The Use of Android Based Multi-representation Test to Profile 4C Skills Based on Experimental Activities Regarding to Gender and Learning Styles - Feranie, Selly; Kaniawati, Dewi Susanti; Suhandi, Andi; Machmudin, Dadang (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2022)
This study aims to see how well Android based multi-representation test to profile 4C skill based on experimental activities on heat transfer topic regarding gender and learning styles A descriptive research to profile the 4C skill students based on gender and learning style. We use fleming’s VAK learning style questionnaire to identify student learning styles. The research subjects were 60 students of class XI MIPA at a public high school in Majalengka Regency, consisting of 20 male students and 40 female students. 33 students (7 boys and 26 girls) had an Auditory learning style, 17 students (8 boys and 9 girls) had a visual learning style and 10 students (5 boys and 5 girls) had a visual learning style. kinesthetic. Research data were analyzed using quantitative descriptive analysis techniques. The results showed that female students have higher 4C skills than male students in each student’s learning style. This result is agreed with previous research. The visual learning style both female and male student have the higher 4C skill than other learning style and agreed with previous results. It can be understood since the application is dominant with visual content. We conclude that Android based multi-representation test has successfully measure 4C skills based on experiment activities. Teachers think that the application has complete features to measure 4C’s students. It is practical tool to get student’s 4C’ profiles easily and quickly. Based on 4C’s students profile have successfully gave feed back for teacher to improve their learning design such as inserting group experiment activity to solve problem. We conclude that Android based interactive test can be an alternative test for profiling Student’s 21st century skill quickly, easily and practically.Keywords: 4c profile, android based multi-representation test, gender and learning style